War As I Knew It - Patton, George S.; Annotated by Harkins, Paul D., Colonel (Boston Houghton Mifflin Company, 1947)
First published in 1947, War as I Knew It is an absorbing narrative that draws from Patton's vivid memories of battle and his detailed diaries, covering the moment the Third Army exploded onto the Brittany Peninsula to the final Allied casualty report. The result is not only a grueling, human account of daily combat and heroic feats$1 (Bincluding a riveting look at the Battle of the Bulge$1 (Bbut a valuable chronicle by one of the most brilliant military strategists in history. Patton's letters from earlier military campaigns in North Africa and Sicily, complemented by a powerful retrospective of his guiding philosophies, further reveal a man of uncompromising will and uncommon character, which made "Georgie" a household name in mid-century America.s
Include Maps and Appendices.
Memoirs of General Patton's campaigns, assembled from his letters and other writings.
Keywords: World War (1939-1945) -- Military campaigns -- Western Front (World War (1939-1945)) -- Africa, North -- Patton, George S. (George Smith), 1885-1945 -- United States -- Generals -- United States, Army